Revisión bibliográfica de protocolos de manejo de Bacillus thuringiensis (bt) en su captura, aislamiento y propagación para su aplicación en la Facultad de CAREN, sector Salache, cantón Latacunga, provincia de Cotopaxi 2021 - Chávez Bolaños, Daniela Mishell (2021)
This work aims to carry out a bibliographic review that records the different methods of capture, isolation and propagation of the entomopathogenic bacterium Bacillus thuringiensis (bt), with the purpose of having filtered information in a database with a bibliographic manager (Mendeley) and in Excel for a better distribution of the information and its easy access. The methodology used in this research begins with the search for information that was based on the subject of study, with the collection of 80 verified documents, including scientific articles, journal articles, theses or book chapters with a restriction of the last 10 years. Of the methods found (Sauka, 2017) affirms that this bacterium is captured through the larvae of an infected insect, it is also collected by soil samples, for its isolation we found two most used methods and that would be applicable for the conditions of Salache as they are by culture media with sucrose, molasses, corn syrup, etc. (Paucar, 2011) and the incubation of infected larvae to be used in bioassays (Instituto Nacional de Salud (Peru) et al., 2002). On the other hand, according to (National Institute of Health (Peru) et al., 2002). For propagation methods, there are liquid culture media for the multiplication of this bacterium, such as substrates based on sweetened milk, whey and even by culture media.